2015
DOI: 10.1021/acs.jmedchem.5b00975
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Orthogonal Multipolar Interactions with Fluorine in Protein–Ligand Complexes

Abstract: Multipolar interactions involving fluorine and the protein backbone have been frequently observed in protein–ligand complexes. Such fluorine–backbone interactions may substantially contribute to the high affinity of small molecule inhibitors. Here we found that introduction of trifluoromethyl groups into two different sites in the thienopyrimidine class of menin–MLL inhibitors considerably improved their inhibitory activity. In both cases, trifluoromethyl groups are engaged in short interactions with the backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 44 publications
2
99
0
Order By: Relevance
“…The visualization of snapshots from the MD trajectory highlight that C―F bond of D744 interacts with a CO moiety of F20 (chain A) of Aβ 42 protofibril through orthogonal multipolar interaction which is consistent with the results reported from molecular docking studies. The optimal geometry and orientation of ligand are important criteria that decide about the feasibility of C―F···CO interactions . The orthogonal geometry of C―F bond relative to the peptide backbone is responsible for these unique types of interactions in the binding region where hydrogen bond interactions do not exist.…”
Section: Resultsmentioning
confidence: 99%
“…The visualization of snapshots from the MD trajectory highlight that C―F bond of D744 interacts with a CO moiety of F20 (chain A) of Aβ 42 protofibril through orthogonal multipolar interaction which is consistent with the results reported from molecular docking studies. The optimal geometry and orientation of ligand are important criteria that decide about the feasibility of C―F···CO interactions . The orthogonal geometry of C―F bond relative to the peptide backbone is responsible for these unique types of interactions in the binding region where hydrogen bond interactions do not exist.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Thes tability of these nanostructures was reported to be higher than expected because of the unique hydrophobicity and lipophilicity of the fluorine atoms,which confer stronger interactions than other noncovalent bonds. [9,10] These studies showed ad ramatic increase in the binding affinity towards most of the proteins and enzymes upon fluorine substitution. [9,10] These studies showed ad ramatic increase in the binding affinity towards most of the proteins and enzymes upon fluorine substitution.…”
mentioning
confidence: 99%
“…In particular, orthogonal multipolar C−F⋅⋅⋅C=O interactions with both peptide backbone and side‐chain carbonyl groups have been described as important for fluorine. Amides are abundant in proteins, and orthogonal multipolar fluorine–amide interactions between ligand fluorines and backbone amides (Figure a) have been reported . The fluorine–amide interaction is proposed to arise from an attractive dipole interaction between the C−F and C=O groups, and the geometric preferences have also been determined in a model system using chemical double‐mutant cycles.…”
Section: Introductionmentioning
confidence: 97%
“…Such distinct fluorophilic environments in proteins are peptide bonds, which can participate in multipolar C−F⋅⋅⋅H−N, C−F⋅⋅⋅C=O, and C−F⋅⋅⋅H−Cα interactions, as well as the side‐chain amide moieties of Asn and Gln . Fluorines enhance ligand affinity by interacting with both the polar electropositive and the hydrophobic groups in proteins . In particular, orthogonal multipolar C−F⋅⋅⋅C=O interactions with both peptide backbone and side‐chain carbonyl groups have been described as important for fluorine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation